In Men With Obesity, T2DM Is Associated With Poor Trabecular Microarchitecture and Bone Strength and Low Bone Turnover - Vigevano, Francesca; Gregori, Giulia; Colleluori, Georgia; Chen, Rui; Autemrongsawat, Vimlin; Napoli, Nicola; Qualls, Clifford; Villareal, Dennis T; Armamento-Villareal, Reina (The journal of clinical endocrinology and metabolism, 2021)
Abstract Introduction Obesity and type 2 Diabetes (T2D) are both associated with greater bone mineral density (BMD) but increased risk of fractures. The effect of the combination of both conditions on bone metabolism, microarchitecture, and strength in the obese population remains unknown. Methods Data from 112 obese men were collected. Bone turnover and biochemical markers were measured by enzyme-linked immunosorbent assay, body composition and BMD at all sites were assessed by dual energy X-ray absorptiometry, whereas bone microarchitecture and strength (stiffness and failure load) were measured by high-resolution peripheral computed tomography. Data were compared among metabolically healthy obese (MHO) and metabolically unhealthy obese (MUHO) with and without T2D and between obese without and with T2D. Results Compared to MHO and MUHO without T2D, MUHO with T2D had significantly lower levels of osteocalcin ((7.49 ± 3.0 and 6.03 ± 2.47 vs 4.24 ± 2.72 ng/mL, respectively, P = 0.003) and C-terminal telopeptide of type I collagen (CTx) (0.28 ± 0.10 and 0.29 ± 0.13 vs 0.21 ± 0.15 ng/mL, respectively, P = 0.02). Dividing our subjects simply into those with and without T2D showed that obese men with T2D had significantly lower levels of osteocalcin (P = 0.003) and CTx (P = 0.005), greater trabecular separation at the tibia and radius (P = 0.03 and P = 0.04, respectively), and lower tibial failure load and stiffness (both P = 0.04), relative to obese men without T2D. Conclusion In men, the combination of obesity and T2D is associated with reduced bone turnover and poorer trabecular bone microarchitecture and bone strength compared to those who are obese but without T2D, suggesting worse bone disease.